2016
DOI: 10.1159/000452415
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin Relaxes Isolated Mesenteric Arteries by Activating the Endothelial Ca<sup>2+</sup>-eNOS Pathway in Rats

Abstract: Aims: Nobiletin, a natural polymethoxylated flavonoid compound, has various beneficial properties, such as anticancer, anti-inflammatory, and antioxidant effects, and it also improves memory. Therefore, we investigated the effects and mechanisms of nobiletin on rat isolated mesenteric arteries (MAs). Methods: We examined vasodilation induced by nobiletin on rat isolated MA rings with a tension study, the expression and activity of endothelial nitric oxide synthase (eNOS) with Western blotting, NO production wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Consistent with these results, nobiletin significantly increased the relaxation of phenylephrine-induced contraction in endothelium-intact rat aorta [33]. In support of this observation, nobiletin has been shown to promote the phosphorylation of eNOS at position Ser-1177 by increasing endothelial [Ca 2+ ]i, thereby increasing NO production and vasodilation in phenylephrineprecontracted mesenteric arteries isolated from rats [34]. In keeping with these findings, nobiletin alleviated iron overload damage in vascular endothelium through increasing eNOS phosphorylation and NO production [35].…”
Section: Differential Effects Of Citrus Flavonoids On Enos Expressionsupporting
confidence: 72%
“…Consistent with these results, nobiletin significantly increased the relaxation of phenylephrine-induced contraction in endothelium-intact rat aorta [33]. In support of this observation, nobiletin has been shown to promote the phosphorylation of eNOS at position Ser-1177 by increasing endothelial [Ca 2+ ]i, thereby increasing NO production and vasodilation in phenylephrineprecontracted mesenteric arteries isolated from rats [34]. In keeping with these findings, nobiletin alleviated iron overload damage in vascular endothelium through increasing eNOS phosphorylation and NO production [35].…”
Section: Differential Effects Of Citrus Flavonoids On Enos Expressionsupporting
confidence: 72%
“…Ikemura et al [26] also provided a clue for anti-hypertensive effects of nobiletin by feeding experiments in SHR rats, but the results were largely observational lacking in mechanistic explanation. Recently, Yang et al reported that nobiletin exhibits relaxation in mesenteric arteries through the calcium-eNOS pathway in endothelium [32]. However, the anti-contractile effect of nobiletin against vasoconstriction has not been reported, to the best of our knowledge.…”
Section: Resultsmentioning
confidence: 99%